Hippocratic oath or hypocrisy? :Doctors at crossroads - Anita,Bakshi (Sage, 2018)
"Medicine was until recently a greatly respected profession supported by trust and faith on one side and compassion and care on the other. However, over the years, the relationship between doctors and patients has suffered. Doctors now find themselves in the news for all the wrong reasons. Labelled as 'murderers', 'knife happy', 'organ stealing thieves' or touts of pharmaceutical giants, they have now lost respect in the eyes of society. When and how did this happen? When did doctors go from being 'Next to God' to maut ke saudagar, as the media is so fond of labelling them? Hippocratic Oath or Hypocrisy?: Doctors at Crossroads is the author's journey as a doctor over three decades, from a young medical student to an experienced paediatrician. She has used her experience to highlight serious issues--demanding patients, prescribing of unnecessary investigations, hospitals run like business houses, the role of big pharmaceutical industries and so on from the point of view of both doctors and patients"--